Exploring richness in design spaces as a multi-level defined construct - Kersten, Wouter; Diehl, Jan Carel; van Engelen, Jo M.L. (FormAkademisk, 2022)
It seems relevant that designers who are dealing with complex societal issues need to be able to assess whether the complexity of the design task has been captured sufficiently. We put forward that assessing the “richness” of intermediate results of a design process can be used for this. We explore the introduction of richness as a multi-level defined construct to create a shared language for this assessment. We created a three-part definition and tested its workability and value for designers. The results demonstrate the workability of considering richness as a multi-level defined construct, and value of using it to assess the richness of an intermediate result of a design process, to inform the decision whether to continue the design process. This exploration can be built upon in various ways.